Psychometric evaluation of Anger Rumination Scale - Besharat, M; Mohammad Mehr, R (Advances in Nursing & Midwifery, 2009)
Background and aim Anger rumination is an inevitable, repetitive and cognitive process which occurs during anger experience, continues after it and increases its duration and severity. Anger rumination is associated with a wide range of psychological disorders, especially emotional ones. The main purpose of this study was to examine the validity and reliability of Anger Rumination Scale (ARS) as an important tool in health studies. Materials and methods 384 students (211 girls and 173 boys) of Tehran University took part in the study by completing Anger Rumination Scale (ARS), Tehran Multidimensional Anger Scale (TMAS), and Mental Health Inventory (MHI). The scale was validated with content, convergent and discriminant validity. Its reliability was measured by test-retest and internal consistency methods. Findings Reliability scores of the scale were satisfactory. Its content validity was calculated with a significant result according to Kendall’s coefficients of concordance for its subscales including angry afterthoughts, thoughts of revenge, angry memories and understanding of causes as well as its total score after reviewing by 10 psychology specialists. The convergent and discriminant validities of the scale were measured based on an expected pattern of correlations between it and the measures of trait-anger, state-anger, anger-in, anger-out, anger-control in, anger-control out, psychological well-being, and psychological distress with significant results. Conclusion It can be concluded that Anger Rumination Scale (ARS) is a valid and reliable scale to measure anger rumination. Keywords: Anger Rumination Scale, Validity, Reliability. *Corresponding Author: Dr. Besharat; Professor of Clinical Psychology, Tehran University, Tehran, Iran. E-mail: besharat@ut.ac.ir